Case Study: Implementation of Video-Based Education to Improve Medication Adherence in Child L with Tuberculosis in Panumbangan - Nugraha, Ilham; Firmansyah, Andan; Supriadi, Dedi (Yayasan Inspirasi El Burhani, 2025)
Introduction: Tuberculosis (TB) is a contagious infectious disease that remains a global health problem, especially in developing countries like Indonesia. Adherence to TB treatment is crucial for therapeutic success, particularly in children who often face challenges in taking medication regularly. One effort to improve adherence is through education using audiovisual media. Objective: To determine the effect of video-based education on medication adherence in children diagnosed with pulmonary tuberculosis. Method: This study used a descriptive case study approach involving one school-aged child with pulmonary TB who exhibited non-adherence. The intervention consisted of video education accessed via YouTube for three consecutive days. Data collection methods included interviews, observation, physical examination, and nursing documentation. Result: After three days of video education intervention, the child’s adherence improved. Initially, the child resisted medication and frequently became upset, but after watching the educational video with their parents, the child began to take the medication willingly. Conclusion: Video-based education is effective in improving medication adherence in children with TB. Educational videos can serve as an engaging and accessible alternative for health promotion, easily accepted by both children and their families.